L' ecologia di Gesù: Il creato e la sua custodia nei vangeli - Gasparro, Lorenzo (Rassegna di teologia, 2022)
The paper aims to show how, beyond appearances, attention to creation and more generally to the sphere of ecology are not at all absent from Jesus’ teaching. A quick survey of some pericopes will show how the Gospels, in narrating the creation, suggests and inspires a relationship between man and nature of perfect communion and mutual integration. A renewed focus on the Jesus-creation relationship not only fills an investigative gap, but also provides some essential keys to correctly understanding the entire biblical treatment of creation, helping to reinvigorate awareness and moral responsibility about it. (English)